1994
DOI: 10.2337/diacare.17.12.1465
|View full text |Cite
|
Sign up to set email alerts
|

Urinary chiro-Inositol Excretion is an Index Marker of Insulin Sensitivity in Japanese Type II Diabetes

Abstract: The urinary excretion of chiro-inositol was much lower in the diabetic patients (32.3 +/- 16.0 mumol/day, means +/- SD) than in the NGT subjects (96.0 +/- 17.6; P < 0.0001) and IGT subjects (58.9 +/- 11.6; P < 0.0001). SI was much lower in the diabetic patients (3.81 +/- 1.49) than in the NGT subjects 6.30 +/- 1.59, P < 0.0005). SG was much lower in the diabetic patients (2.14 +/- 0.56) than in the NGT subjects (3.07 +/- 0.38, P < 0.0001). There was a significant correlation between urinary chiro-inositol excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
1
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 8 publications
8
66
1
2
Order By: Relevance
“…In a collaborative study with our Japanese colleagues we demonstrated that, as subjects progressed from normal glucose tolerance to impaired glucose tolerance to type II diabetes, urine chiro-inositol decreased progressively (57). These data and data from Rhesus monkeys (Table 3) suggest that the chiro-inositol deficiency and imbalance with myo-inositol are related more directly to the insulin resistance per se rather than to the type II diabetes.…”
Section: Inositol Imbalance and Insulin Resistancementioning
confidence: 57%
“…In a collaborative study with our Japanese colleagues we demonstrated that, as subjects progressed from normal glucose tolerance to impaired glucose tolerance to type II diabetes, urine chiro-inositol decreased progressively (57). These data and data from Rhesus monkeys (Table 3) suggest that the chiro-inositol deficiency and imbalance with myo-inositol are related more directly to the insulin resistance per se rather than to the type II diabetes.…”
Section: Inositol Imbalance and Insulin Resistancementioning
confidence: 57%
“…In human urine (17), monkey urine (18), genetic G͞K type 2 diabetic rat urine (19), G͞K rat muscle, liver, and kidney (20), and human type 2 diabetic muscle (21), the level of chiro-inositol is decreased and myo-INS content increased compared to controls. The decrease in urinary chiro-inositol in humans (22) and monkeys (18) was inversely correlated to the degree of insulin resistance. Administration of DCI to streptozotocin type 2 diabetic rats (23), monkeys (24), and humans (25,26) effectively decreased hyperglycemia and hypertriglyceridemia (HTG).…”
mentioning
confidence: 92%
“…Insulin resistance has been linked to decreased urinary excretion of chiro-inositol (a component of the putative D-chiro-inositol phosphoglycan mediator) in primates 47 and in humans with impaired glucose tolerance. 48 The amount of chiro-inositol in muscle is lower in subjects with type 2 diabetes mellitus than in normal subjects Administration of D-Chiro-insitol has been demonstrated to improve glucose tolerance, decrease serum androgens and improve ovulation in PCOS patients. 49 Nestler J E reported improvement in the insulin sensitivity by D-chiro-inositol hence improves ovulatory function and decreases serum androgen concentrations along with blood pressure and metabolic parameters such as plasma triglyceride concentrations.…”
Section: D-chiro-inositolmentioning
confidence: 99%